Resource‐ratio theory predicts mycorrhizal control of litter decomposition. Issue 3 (15th July 2019) - Smith, Gabriel R.; Wan, Joe
Summary: Ecosystems with ectomycorrhizal plants have high soil carbon : nitrogen ratios, but it is not clear why. The Gadgil effect, where competition between ectomycorrhizal and saprotrophic fungi for nitrogen slows litter decomposition, may increase soil carbon. However, experimental evidence for the Gadgil effect is equivocal. Here, we apply resource‐ratio theory to assess whether interguild fungal competition for different forms of organic nitrogen can affect litter decomposition. We focus on variation in resource input ratios and fungal resource use traits, and evaluate our model's predictions by synthesizing prior experimental literature examining ectomycorrhizal effects on litter decomposition. In our model, resource input ratios determined whether ectomycorrhizal fungi suppressed saprotrophic fungi. Recalcitrant litter inputs favored the former over the latter, allowing the Gadgil effect only when such inputs predominated. Although ectomycorrhizal fungi did not always hamper litter decomposition, ectomycorrhizal nitrogen uptake always increased carbon : nitrogen ratios in litter. Our meta‐analysis of empirical studies supports our theoretical results: ectomycorrhizal fungi appear to slow decomposition of leaf litter only in forests where litter inputs are highly recalcitrant. We thus find that the specific contribution of the Gadgil effect to high soil carbon : nitrogen ratios in ectomycorrhizal ecosystems may be smaller than predicted previously.